Infratentorial Microbleeds. Issue 7 (July 2015) - Arkink, Enrico B.; Terwindt, Gisela M.; de Craen, Anton J.M.; Konishi, Junya; van der Grond, Jeroen; van Buchem, Mark A.; Ferrari, Michel D.; Kruit, Mark C.
<x xml:space="preserve">Abstract</x> Background and Purpose— Migraine is a risk factor for clinical stroke and for subclinical white matter hyperintensities and infratentorial infarcts. These subclinical lesions are linked to small-vessel pathology. Cerebral microbleeds (CMBs) are another biomarker of small-vessel disease but have not yet been studied in migraine. Methods— Identification of CMBs in 63 migraineurs (25 with aura/35 without aura/3 unknown aura status) and 359 controls (aged, 73–85 years) from the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER) magnetic resonance imaging study. We assessed the modifying role of migraine in the co-occurrence of CMBs, infarcts, and white matter hyperintensity-load. Results— Infratentorial microbleeds were more prevalent in migraine without aura patients than controls (14% versus 4%). Prevalence of other CMBs, infarcts, and white matter hyperintensities did not differ between groups. Migraineurs with CMBs had more often infarcts than controls with CMBs (65% versus 43%). In comparison with controls with infarcts, migraineurs with infarcts had more commonly CMBs (55% versus 30%). Conclusions— Migraine, notably without aura, is associated with infratentorial CMBs at older age. CMBs and infarcts co-occur more often in migraine than in controls. This supports the hypothesis of small-vessel involvement in migraine pathophysiology.